Fundraising Innovation in Mosque Development through a Meat Subsidy Program on Lombok Island - Fatoni Ahmad; Wahyu Trisno Aji (ASTEEC, 2025)
This paper aims to explain that the existence of a mosque is not merely as a place for performing daily prayers, but also as a space for fostering community welfare. This study employs a qualitative method with a case study approach. Data collection focuses on in-depth interviews, direct observation of the meat subsidy program conducted during the holy month of Ramadan in 2025, as well as documentation from relevant literature, interviews, and program records. The study examines fundraising innovation in mosque development through a beef meat subsidy program implemented during the holy month of Ramadan. Al Muhajirin Mosque, located in Teliah Hamlet, South Sakra Village, Sakra District, East Lombok Regency, West Nusa Tenggara, initiated a program by utilizing mosque construction funds to purchase beef, which was then subsidized for the local community. The meat could be purchased through installment payments, with the payment deadline extending until the beginning of the following Ramadan. This initiative demonstrates that the mosque does not solely function as a religious space for congregational worship, but also serves as an institution that contributes to the socio-economic welfare of the community, even though the impact generated is not yet significantly large.